Digital Decade: How the EU Shapes Digitalisation Research (Normsetzung und Entscheidungsverfahren – Schriftenreihe des Weizenbaum-Instituts für normative Wissenschaften, 2025)
Over the last ten years; numerous pieces of EU legislation have been adopted in the field of digital law; including the AI Act; the Digital Services Act and the Digital Markets Act. These complex but sometimes difficult to understand legal acts play an important role in research and everyday life. In this volume; legal scholars and experts present the key EU legal acts that are relevant to social scientists; students and the general public. The volume also aims to stimulate a greater exchange between the social sciences and law; from which both disciplines can benefit. With contributions by Dr. Adelaida Afilipoaie | Valerie Albus | Dr. Lucie Antoine | Jascha Bareis; M.A. | Prof. Dr. Catrien Bijleveld; LL.M. | Jorge Constantinos | Dr. Max Van Drunen; M.Z. | Rita Gsenger; M.A.; M.Sc.| Prisca von Hagen | Liza Herrmann | Julia Krämer | Eyup Kun | Dr. Lucas Lasota | Lisa Markschies | Heritiana Ranaivoson | Nik Roeingh | Jun.-Prof. Dr. Hannah Ruschemeier | Pascal Schneiders | Marie-Therese Sekwenz | Lisa Völzmann | David Wagner